The information from JAKIM staff of product produce by muslim / Muhammad Solehuddin Khadzait - Khadzait, Muhammad Solehuddin (2018)
Malaysia is a country with many races namely Malays, Chinese, Indian, and religion namely Islam, Christianity, Buddhism and others. Statistics from the Malaysian statistics department stated that in 2018 the population of Malaysia was 32.4 million (Jabatan Perangkaan Malaysia, 2018). The growth rate is estimated to increase by 1.1%. If ethnicity is Bumiputra population is 20.07 million, the Chinese population is 6.69 million, population of India is 2.01 million and other population is 0.29 million. With the population, created a variety of products for sale and used by the public every day. These products are not only from Islamic companies but also from non- Islamic companies. The purpose of this research is to analyse the information from JAKIM staff of product produce by Muslim. The first objective of this research is to identify the products produce by Muslim companies, second objective is to know the information of JAKIM staff about product which one produce by Muslim and non- Muslim through questionnaire and third objective is to suggest the right method encourage JAKIM staff to use and buy products produce by Muslim. Last but not least, there are few recommendations from these findings to improve and encourage JAKIM staff and society to support products made by Muslim which several program such as expo products produce by Muslim, promotion and others.